IMPLEMENTASI AKAD MURABAHAH PADA BANK BNI 46 SYARIAH DITINJAU DARI HUKUM ISLAM: Studi Kasus di Kantor Cabang Fatmawati - Muhammad Aswin; Irvan Iswandi (Jurnal Penelitian Multidisiplin Ilmu, 2022)
The research problems are how does the Murabaha mechanism work at Bank BNI 46 Syariah Fatmawati Branch Office in South Jakarta? Does Murabaha contract at Bank BNI 46 Syariah Fatmawati Branch Office complies with Islamic law? The objectives of the study are to know how the Murabaha contract mechanism works and whether the Murabaha contract at Bank BNI 46 Syariah Fatmawati Branch Office in South Jakarta complies with Islamic law or not. This study used qualitative method. The data sources were primary and secondary data obtained by interviews, observation, and documentation. Data analysis begins with data collection, data reduction, followed by tabulating data and analyzing existing data in order to find results from research as answer to the predetermined research problems. The results showed that Murabaha contract mechanism can be run by customers applying for financing by bringing the necessary files to the bank, checking data / data verification in order to obtain data completeness, field surveys, evaluating needs and financing decisions, applying contracts and binding collateral as well as disbursement financing. This study also found that the Murabaha contract process managed by Bank BNI 46 Syariah Fatmawati Branch Office was in accordance with the National Sharia Board (DSN) fatwas of the Indonesian Ulema Council (MUI) No: 04 / DSNMUI / IV / 2000, and was done using four indicators namely sale and purchase agreements, profit margins, payment methods, and goods receipt.